2021
DOI: 10.3389/fphar.2021.706580
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Analysis of Peripheral Blood Reveals a Novel B-Cell Subset in Renal Allograft Recipients With Accommodation

Abstract: Background: Kidney transplantation (KTx) is a preeminent treatment for end-stage renal disease (ESRD). After the application of immunosuppressants (IS), renal allograft recipients could reach a state called accommodation which means they are neither rejected nor infected. This study aimed to describe the details of this immune accommodation and reveal a novel mechanism of IS on immune cell subpopulations.Methods: We analyzed multiple cell subgroups and their gene expression of peripheral T, B, myeloid, and NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Features conserved among the data sets were identified using study of origin as the grouping variable. Cell type specificity of the markers was further confirmed using several recent publications 28 , 37 , 51 78 . As a result, 9 and 27 cell types were found for level 1 and 2 of annotation, respectively (Supplementary Fig.…”
Section: Methodssupporting
confidence: 52%
“…Features conserved among the data sets were identified using study of origin as the grouping variable. Cell type specificity of the markers was further confirmed using several recent publications 28 , 37 , 51 78 . As a result, 9 and 27 cell types were found for level 1 and 2 of annotation, respectively (Supplementary Fig.…”
Section: Methodssupporting
confidence: 52%
“…In our previous study, we found that anti-HLA. A2 antibody titers increased more steeply after two skin grafts than they did after the first exposure to HLA.A2 antigen [13]. This finding indicates that memory B cells that formed after the first exposure to HLA.A2 antigen rapidly expand and differentiate into plasma cells after the second exposure.…”
Section: Discussionmentioning
confidence: 78%
“…Meanwhile, single-cell RNA sequencing (scRNA-seq) has emerged as a new technique to comprehensively analyze the transcriptome of each immune cell population at a single-cell level; it also compensates for the limitations of traditional bulk RNA sequencing and microarrays [9,10]. ScRNA-seq deepens our knowledge of the underlying immune cell types and states, as well as cell type-specific transcriptomic signatures that are associated with autoimmune diseases [11,12] and KT recipients (KTRs) [13]. In our previous study using scRNA-seq analysis of human peripheral blood samples, we not only found consistent results from prior studies but also discovered new subpopulations of immune cells and the molecular characteristics that are involved in immune tolerance in KTRs [14].…”
mentioning
confidence: 99%
“…These patients had especially lower number of activated CD127 + B cells compared with healthy controls. 151 Together, these studies show that single-cell approaches are helpful to detect changes in immune cell composition following immunosuppression. Future studies may further examine changes not only in cell numbers, but also in the expression of specific genes following immunosuppression.…”
Section: Studying the Effect Of Immunosuppressive Therapiesmentioning
confidence: 90%
“…The effect of immunosuppressive therapies following organ transplantation can be studied using single-cell approaches. 122,[148][149][150][151] For example, treatment of PBMCs with tacrolimus has been shown to result in a decreased number of immature B cells. 148 However, since this flowcytometric study included only a limited number of parameters, techniques such as CyTOF and scRNAseq can provide more extensive information.…”
Section: Studying the Effect Of Immunosuppressive Therapiesmentioning
confidence: 99%